Peran Dan Tantangan BPR (Bank Perkreditan Rakyat) Saat Ini - I Gst. Ngr. Alit Asmara Jaya (Universitas Mahendradatta Denpasar, 2020)
According to Law no. 07 of 1992 concerning Banking, there are 2 types of banks in Indonesia, namely Commercial Banks and BPRs. BPR in Indonesia as of November 2019 according to the Indonesian Banking Statistics Report, amounting to 1,552. Looking at the history of its establishment, BPRs have existed since the colonial era and have close relationships with rural / small communities. Given this, to improve services to the community, with government policies through Pakto 88 and Kepres No. 38 of 1988 regarding the establishment of BPR made easier.Currently, BPRs face tough challenges amid the rapidly changing external industrial environment such as competition, government policies, macroeconomic conditions, fintech developments and others. This development has indirectly reduced the profitability performance of rural banks over the past 5 years. However, on the other hand, during the last 5 years, BPRs have been able to show business development and support real sector financing, especially MSMEs. This paper aims to analyze the challenges faced, the role and efforts to develop BPRs so that in the future BPRs will continue to develop and play a role in supporting the progress of the Indonesian economy.